Experimental Study of Freeze-Thaw/Water Compound Erosion and Hydraulic Conditions as Affected by Thawed Depth on Loessal Slope - Wang, Wei; Li, Zhanbin; Yang, Rui; Wang, Tian; Li, Peng (Frontiers in Environmental Science, 2020)
Freeze-thaw cycles have significant influences on slope erosion processes. In this study, simulated rainfall laboratory experiments were implemented to investigate erosion processes and the relationship between the soil loss rate and hydraulics conditions under different thawed depths and rainfall intensities. The results indicated that linear regression could be used to describe the relationship between the soil loss rate and runoff time. Soil loss rate, as measured by the curve slope k (represented the increase rate in the soil loss rate), generally increased with runoff time over different thawed depths across all rainfall intensities.The k values generally increased with rainfall intensity from 0.6 mm/min to 1.2 mm/min, with the exception of the 4 cm thawed slope, for which the k values initially increased before decreasing with rainfall intensity from 0.6 mm/min to 1.2 mm/min. The mean soil loss rate and range also increased with thawed depth under the same rainfall intensity. Finally, the interaction of rainfall intensity and thawed depth had the greatest effect on soil loss rate, while stream erosion power was the hydraulic parameter that exhibited the best soil loss rate prediction performance. The results presented herein improve the understanding of the response of freeze-thaw/water compound erosion to hydraulic conditions.